1993
DOI: 10.2136/sssaj1993.03615995005700050032x
|View full text |Cite
|
Sign up to set email alerts
|

Agroecosystem Approach to Soil and Crop Management Research

Abstract: Research techniques that have greatly advanced agronomic science in the 20th century, and have enhanced our knowledge of cause and effect, have been accompanied by reductionism. As a result, much valuable research has been accomplished, but less synthesis of results has occurred that provides answers to landscape-level research questions. We propose that a systems approach to the study of soil and crop management problems is a useful technique that tests our present research knowledge in a way that answers pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
113
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 0 publications
2
113
0
1
Order By: Relevance
“…Dryland farming is limited by water availability; therefore, crop water productivity is among the required measures of a sustainable dryland crop rotation (Huang et al, 2003;Pala et al, 2007;Peterson et al, 1993Peterson et al, , 1996. Stratified use of soil water by component crops and increased interception of annual precipitation are among some of the mechanisms that were described to have contributed to better crop water productivity with the selected rotations in previous research.…”
Section: Rotationmentioning
confidence: 94%
See 1 more Smart Citation
“…Dryland farming is limited by water availability; therefore, crop water productivity is among the required measures of a sustainable dryland crop rotation (Huang et al, 2003;Pala et al, 2007;Peterson et al, 1993Peterson et al, , 1996. Stratified use of soil water by component crops and increased interception of annual precipitation are among some of the mechanisms that were described to have contributed to better crop water productivity with the selected rotations in previous research.…”
Section: Rotationmentioning
confidence: 94%
“…Th e most common dryland rotation in the Great Plains has been a 2-yr wheat-fallow system (Anderson et al, 1999;Assefa et al, 2014;Hansen et al, 2012;Norwood, 2000). Drawbacks of the wheat-fallow rotation include soil quality degradation, loss of organic matter, low precipitation use efficiency, and a relatively small contribution in breaking weed cycles (Anderson et al, 1999;Peterson et al, 1993). Improvements in fertilizer, pesticide, and tillage technologies have enabled inclusion of warm-season crops, such as sorghum, corn (Zea mays L.), soybean [Glycine max (L.) Merr.…”
mentioning
confidence: 99%
“…Intensification of dryland cropping systems has resulted in pronounced increases in biomass and grain production on an annual basis across much of the Central and Southern Great Plains (Peterson et al, 1993(Peterson et al, , 1996Norwood, 1994;Jones and Popham, 1997). Peterson and Westfall (2004) found that intensification of cropping systems increased net return to producers in eastern Colorado by 25 to 45% compared with wheatfallow.…”
mentioning
confidence: 99%
“…A four-factor study was initiated in Colorado to provide answers to questions consistently being raised by scientists and producers by creating an experiment that simultaneously addressed cropping system, landscape position, precipitation gradient, and time interactions (Peterson et al, 1993). The overarching research objective of the study was to identify sustainable dryland cropping systems that would: (i) maximize precipitation use efficiency, (ii) improve soil productivity, and (iii) increase economic return to farmers.…”
Section: Landscape and Climate Interaction Researchmentioning
confidence: 99%